#TITLE_ALTERNATIVE# - ABDURRAHMAN (nim:10511031), ZULFIKAR
Indonesia is a country which has the fourth longest coastline in the world. However, with a favorable geographic until today Indonesia is still listed as a salt importing country with an average of over 1.5 million tons annually. This condition is very alarming because salt is a basic human need and has many uses. In addition to consumption, salt is also useful for a variety of industries such as the food industry, pharmaceutical industry, and many more depending on the level of purity. To determine the krosok salt content from salt farmers, first measurements were taken using AAS (Atomic Absorption Spectrophotometry) and EDS (Energy Dispersive X-Ray Spectroscopy). As a result, most present in krosok salt beside Na were Ca and Mg that were as much as 3.89% and 2.58%. Based on research Farrukh et al., the reduction of concentration Ca and Mg is done by adding Na2CO3 and NaOH to resulting precipitate of CaCO3 and Mg(OH)2. To get good results, the optimization of time and temperature stirring was done. The precipitation of Ca and Mg were the most optimal at 120 minutes and 105 Ã‚Â°C. The precipitation process is then performed by adding Na2CO3 and NaOH together using the optimum parameters. The concentration of Ca and Mg were measured using AAS and EDS. AAS results showed that the concentration of Ca and Mg decreased to 0.0107% and 0.0019%, while the results of EDS showed there were no longer an element of Ca and Mg.